The case for a rectangular format space telescope for finding exoplanets - Newberg, Heidi Jo; Swordy, Leaf; Barry, Richard K.; Cousins, Marina; Nish, Kerrigan; Rickborn, Sarah; Todeasa, Sebastian (Frontiers in Astronomy and Space Sciences, 2025)
We suggest that rectangular primary-mirror telescopes provide a clearer path to discovering habitable worlds than other designs currently being pursued. We show that a simple infrared (λ∼10 μm) telescope design with a rectangular mirror 20 m in length and 1 m in width, combined with technology already developed for JWST, can discover ∼11 habitable exoplanets and measure ozone in their atmospheres in a mission of ∼1 year. A mission of ∼3.5 years could plausibly discover ∼27 habitable exoplanets closer than 10 pc to the Earth, and determine whether there is ozone in their atmospheres. A square primary mirror with the same collecting area cannot resolve exoplanets that are within 0.23″ of the host star, making it impossible to detect most of the nearby Earth-like exoplanets. The idea of collecting light with a high aspect ratio rectangular mirror could be used at any wavelength. It is particularly useful for measuring point sources with very small angular separations, as is required for exoplanet observation.